A sustainable synthesis of 2-aryl-3-carboxylate indolines from N-aryl enamines under visible light irradiation. Issue 59 (7th July 2017) - Wu, Cheng-Juan; Cao, Wen-Xiao; Lei, Tao; Li, Zhi-Hua; Meng, Qing-Yuan; Yang, Xiu-Long; Chen, Bin; Ramamurthy, Vaidhyanathan; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : With visible light irradiation of a catalytic amount of Ir(ppy)3 at room temperature, a number of N -aryl enamines were transformed into their corresponding indoline products in good to excellent yields without requiring any extra additives. Abstract : With visible light irradiation of a catalytic amount of Ir(ppy)3 at room temperature, a number of N -aryl enamines were transformed into their corresponding indoline products in good to excellent yields without requiring any extra additives. This is the first example of the synthesis of indolines via the intramolecular cyclization of enamines under visible light irradiation.